The design,development and evaluation of a web-based Arabic vocabulary learning games prototype in IIUM - Sahrir, Muhammad Sabri; Md Ghalib, Mohd. Feham; Osman, Nurulhuda (2011)

(untitled)
This innovation features an online Arabic vocabulary learning games prototype specifically designed for Arabic elementary learners at the pre-university level from the Centre for Foundation Studies (CFS), International Islamic University Malaysia (IIUM). The innovative process begun with the literature analysis of 3 theories based on the work of Nation (2003), Prensky (2001) and Mayer (2001). The design and development of this game-based learning prototype are modelled on the methods and approaches of design and development research (Richey & Klein, 2007) or formerly known as developmental research (Richey, Klein & Nelson, 2004). This method is also known as designed case (Reigeluth & Frick, 1999), design-based research (Reeves, 2006 & Herrington, et. al, 2007), formative research (Nieveen, 2007), and design research (Bannan-Ritland, 2003; Van der Akker, 2007). This game-based learning prototype enables lecturers and students access to additional Arabic language learning aid, in a gaming application, complementing traditional learning methods. It facilitates vocabulary enhancement through a compendium and variety of games (34 games) in the online environment and supported with open sources of online dictionary, online translator and games glossary (in English and Arabic). The prototype provides a new learning experience for students who have been through a traditional Arabic teaching and learning methods, by immersing into the attractive, interesting and interactive game-based learning environment.